Chimeric tumor modeling reveals role of partial PDL1 expression in resistance to virally induced immunotherapy. Issue 1 (16th January 2019) - Bartee, Mee Y.; Dryja, Parker C.; Bartee, Eric
Abstract : Expression of PDL1 on the surface of tumor cells can blunt the efficacy of many cancer immunotherapies. For example, our lab has previously shown that tumors derived from malignant cells incapable of expressing PDL1 are highly susceptible to immunotherapy induced by oncolytic virus treatment while tumors derived from PDL1 capable cells are highly resistant. In patient biopsies, however, expression of PDL1 on malignant cells is often not uniform with some cells expressing PDL1 while others do not. Importantly, how this partial PDL1 positivity influences the outcomes of immunotherapy remains largely unknown. In the current work, we expand on our previous findings by generating partially PDL1 positive tumors in immune competent animals and asking what percentage of tumor cells must express PDL1 for a tumor to become functionally resistant to oncolytic treatment. Our results indicate that the responsiveness of partially PDL1 + tumors correlates linearly with the percentage of PDL1 capable cells present at the initiation of treatment. Additionally, we observe that tumors which relapse after treatment display a significant increase in the numbers of PDL1 capable cells present suggesting that specific editing of mixed tumors might play a role in disease relapse. These data indicate that varying levels of PDL1 expression can play a significant role in the outcomes of oncolytic immunotherapy and challenges the concept that tumors should be viewed as simply PDL1 + or PDL1 − .